Knowledge Regarding Attention Deficit Hyperactivity Disorder among School Teachers in a Secondary School (MedS Alliance Journal of Medicine and Medical Sciences, 2022)
INTRODUCTION: Attention deficit hyperactivity disorder (ADHD) is one of the most common behaviours and emotional problem arises in school age children. Teachers can play a key role in identifying and supporting students with this disorder. In order to achieve this role, it is vital for teachers to have obvious knowledge about this disorder. The aim of this study was to assess knowledge regarding Attention deficit hyperactivity disorder among school teachers.MATERIALS AND METHODS: Descriptive study method was used; altogether 70 samples from Prabhat secondary school teachers were selected by using of census sampling technique. Most of them recognized attention deficit hyperactivity disorder was behavior and emotional problem which was arise in school age period. Similarly, Maximum response about symptoms were forgetfulness and difficulty engaging in non-action activities. Maximum respondents had answered for management way of Attention deficit hyperactivity disorder was motivational therapy.RESULTS: The findings of the study revealed that majority 88.3 % of the respondents had poor knowledge and 11.7% had moderate knowledge regarding attention deficit hyperactivity disorder. The study also showed that the variables such as age, sex, marital status, educational level and teaching experience were not significantly related to knowledge on attention deficit hyperactivity disorder.CONCLUSIONS: This study concluded that the majority of respondent had poor knowledge about Attention deficit hyperactivity disorder. Variables such as age, sex, marital status, educational level and teaching experience were not significantly related to knowledge on attention deficit hyperactivity disorder.